Australian national ocean bottom seismograph fleet advances conventional exploration - Gavrilov, Alexander; Goncharov, A.; Malinowski, M.; Seculic, D.; Cooper, A.; Chia, P.; Paskos, G. (Media Dynamics, 2017)
A fleet of new Australian ocean bottom seismographs (OBSs) have broadband frequency range, and similar instruments are available at only five or six institutions globally. These OBSs are multi-purpose devices able to record passive-source seismic data (earthquakes, ambient noise) as well as active-source (airgun generated) data and, at the same time, to monitor seismic survey noise and whale calls for environmentally responsible exploration. OBS data collected during commercial seismic surveys in Australian waters prove that it is possible to image the velocity distribution of the whole crust and upper mantle from analysis of both reflected and refracted phases generated by an industry-standard broadband airgun array. This means that valuable information on a regional scale can be obtained as a by-product of commercial seismic surveys. Three-component recording capability of OBSs allows analysis of S-waves in addition to the P-waves that are conventionally used in marine reflection surveys.